Recent advances in the role of autophagy in bone metabolism - SUN Bin; WANG Zuolin (Kouqiang hemian waike zazhi)
The balance of bone metabolism depends on the balance between bone formation by osteoblasts and bone resorption by osteoclasts. The disruption of this balance has been shown to have a direct contribution to the onset of bone metabolic disorders. Recent evidence suggests that autophagy may play an important role in regulating the proliferation, differentiation and apoptosis of osteoblasts and osteoclasts. This article reviews the relevant researches on autophagy in regulating the functions of osteoblasts and osteoclasts.